AKTUALISASI PRINSIP GOOD GOVERNANCE PADA PENGEMBANGAN SUMBER DAYA MANUSIA DI PEMERINTAH PROVINSI BALI - Putu Arie Anggadyasa; Luh Putu Mahyuni; I Wayan Ruspendi (Media Bina Ilmiah, 2023)
Weaknesses in public services are centered on human resource (HR) factors and bureaucratic culture. Improving the quality of human resources for public services can be realized by applying the principles of good governance. The principles of good governance will be appropriate if actualized in the implementation of human resource development through the CPNS level, especially in regional government. The implementation of good governance in the formation of the character of human resources in public services is based on four pillars which include: (1) Role of law; (2) Transparent; (3) Equity; (4) Accountability. So that the aims of this study are: (1) to gain knowledge and an overview of the Basic Training for Candidates for Civil Servants (Latsar CPNS), as well as to analyze the application of the principles of Good Governance in the process; (2) identify the factors that influence the process of actualizing the principles of Good Governance; and (3) identify the factors that cause obstacles in the process of actualizing the principles of good governance. In this study using a qualitative descriptive approach using interviews and documentation data collection techniques. The data analysis technique used is an interactive model analysis. The actualization of the principles of Good Governance in the implementation of basic training for Candidates for Civil Servants in the Province of Bali in terms of rule of law, transparency, equity and accountability is going well. This can be seen from the start of the planning, implementation of training, until the closing has been going well. There are several factors that influence the actualization of the principles of good governance in the implementation of basic training for Candidates for Civil Servants in the Provincial Government of Bali, namely the accreditation of the basic training program for Prospective Civil Servants as the implementation of good governance from planning to synergy among all elements of implementation, and surveys of satisfaction with organizers as a measuring tool for service testimonials provided to participants to be able to become a service evaluation. The suggestions based on the results of this research are: 1) management of training and training officer courses for all organizer elements; 2) equal perception of all elements of the organizers; 3) Organizational patterns of coordination and communication that are hierarchical and organized; 4) Training in digital literacy for each organizer element as digital accounting in training; 5) Information dissemination of well-organized training implementation using electronic media; 6) Increasing the supervision of picket officers through digital attendance. 7) It is necessary to recruit Widyaiswara to complete the existing formation; 8) compile material for additional modules related to the principles of good governance; 9) Carrying out an increase in Widyaiswara competence through the thematic Good Governance Core Value ASN Workshop; 10) Facilities in the form of a 24-hour service center for training participants; 11) Public areas; 12) Facilities that are friendly to pregnant women and persons with disabilities